A multicentre, randomised, double blind, placebo controlled phase II study of subcutaneous interferon beta-1a in the treatment of patients with active rheumatoid arthritis. Issue 1 (8th July 2004) - van Holten, J; Pavelka, K; Vencovsky, J; Stahl, H; Rozman, B; Genovese, M; Kivitz, A J; Alvaro, J; Nuki, G; Furst, D E; Herrero-Beaumont, G; McInnes, I B; et al.
Abstract : Objective: To assess the efficacy of interferon beta (IFNβ) in combination with methotrexate in treatment of patients with rheumatoid arthritis. Methods: 209 patients with active rheumatoid arthritis, who had been on methotrexate for at least six months and at a stable dose for four weeks before study entry, were randomised in double blind fashion to receive placebo (0.05 ml or 0.5 ml), IFNβ 2.2 μg (0.05 ml), or IFNβ 44 μg (0.5 ml), given subcutaneously three times weekly for 24 weeks. The primary efficacy measure was a change in radiological scores at week 24. The secondary endpoint was the proportion of patients who met the ACR 20% improvement criteria at the end of the study. Synovial biopsy specimens were obtained before and after treatment from a subset of patients. Immunohistochemistry was used to detect the presence of inflammatory cells and the results were measured by digital image analysis. Collagen crosslinks were measured in urine at different times throughout the study. Results: Analysis of radiological scores and clinical variable showed no changes in any of the groups, and there were no differences between the groups. On microscopic analysis of synovial tissue there was no significant change in the scores for infiltration by inflammatory cells after IFNβ treatment. Urinary levels of collagen crosslinks were unchanged between the treatment groups. Conclusions: At the doses tested, treatment with IFNβ three times weekly in combination with methotrexate did not have a clinical or radiological effect in patients with rheumatoid arthritis.